2022
DOI: 10.3389/fendo.2022.923925
|View full text |Cite
|
Sign up to set email alerts
|

N-terminal BET bromodomain inhibitors disrupt a BRD4-p65 interaction and reduce inducible nitric oxide synthase transcription in pancreatic β-cells

Abstract: Chronic inflammation of pancreatic islets is a key driver of β-cell damage that can lead to autoreactivity and the eventual onset of autoimmune diabetes (T1D). In the islet, elevated levels of proinflammatory cytokines induce the transcription of the inducible nitric oxide synthase (iNOS) gene, NOS2, ultimately resulting in increased nitric oxide (NO). Excessive or prolonged exposure to NO causes β-cell dysfunction and failure associated with defects in mitochondrial respiration. Recent studies showed that inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 89 publications
0
2
0
Order By: Relevance
“…The bromodomain‐containing protein BRD4 recognises and directly engages acetylated H3K27, thereby serving as a molecular scaffold that facilitates the recruitment of transcription factors to chromatin 40 . Additionally, multiple studies have shown that BRD4 interacts with NF‐κB p65 to activate transcription 41,42 . Therefore, we hypothesised that the H3K27ac reader BRD4 may scaffold the interaction between the NLRP3 promoter and transcription factor p65 to drive NLRP3 expression.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The bromodomain‐containing protein BRD4 recognises and directly engages acetylated H3K27, thereby serving as a molecular scaffold that facilitates the recruitment of transcription factors to chromatin 40 . Additionally, multiple studies have shown that BRD4 interacts with NF‐κB p65 to activate transcription 41,42 . Therefore, we hypothesised that the H3K27ac reader BRD4 may scaffold the interaction between the NLRP3 promoter and transcription factor p65 to drive NLRP3 expression.…”
Section: Discussionmentioning
confidence: 97%
“… 40 Additionally, multiple studies have shown that BRD4 interacts with NF‐κB p65 to activate transcription. 41 , 42 Therefore, we hypothesised that the H3K27ac reader BRD4 may scaffold the interaction between the NLRP3 promoter and transcription factor p65 to drive NLRP3 expression. Our data revealed that H3K27ac forms a complex with phosphorylated P65 in a BRD4‐dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin D induces cellular autophagy while inhibiting streptozotocin-induced β-cell apoptosis, increasing insulin secretion and increasing β-cell resistance to cellular stresses encountered in hyperglycemic states ( 55 ). Excessive or prolonged exposure to nitric oxide leads to β-cell dysfunction, whereas vitamin D induces and maintains high levels of the A20 gene protein and reduces nitric oxide levels, thus serving to protect β-cell function ( 56 ).…”
Section: Vitamin D and The Pathogenesis Of Diabetesmentioning
confidence: 99%
“…In the IL-6 Amp disease model, obesity, injury, and infection trigger chronic inflammation and a systemic cytokine storm, which is enhanced by interactions between local non-immune cells and infiltrating immune cells [16]. A prominent example of IL-6 Amp is also seen in Coronavirus disease 2019 (COVID- 19), which is triggered by severe acute respiratory syndrome coronavirus 2 (SARS-CoV2) infection [16]. Consistent with the significance of hIL-6 in disease development, a humanized monoclonal antibody against the hIL-6 receptor, tocilizumab, has proven successful in treating Castleman's disease as well as COVID-19 [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…The bromodomain and extraterminal domain (BET) family proteins, such as bromodomain containing 4 (BRD4), are transcription regulators that localize to cellular enhancer and promoter loci and control the transcription of a wide range of proinflammatory genes. BRD4 regulates transcription by recognizing acetylated histone tail and interacts with transcription factors such as NF-κB p65 and transcription elongation complex [19]. This mechanism facilitates the phosphorylation of RNA Polymerase II (RNAPII) and promotes transcription initiation and elongation.…”
Section: Introductionmentioning
confidence: 99%